2008
DOI: 10.1158/1078-0432.ccr-07-1066
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Antigen Processing Components TAP and Tapasin Elicits Enhanced Tumor-Free Survival

Abstract: Purpose: Tpn is a member of the MHC class I loading complex and functions to bridge the TAP peptide transporter to MHC class I molecules. Metastatic human carcinomas often express low levels of the antigen-processing components Tapasin and TAP and display few functional surface MHC class I molecules. As a result, carcinomas are unrecognizable by effector CTLs. The aim of this study is to examine if Tapasin (Tpn) plays a critical role in the escape of tumors from immunologic recognition. Experimental Design: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…[19][20][21]24 A former study has demonstrated that restoring tapasin gene expression in a mouse tumor model using viral vector transduction improved survival of model mice bearing lung carcinoma. 28 In this study, we generated human lung and colon cancer variants that express TAAs, survivin, or cep55, genetically lacking tapasin protein expression. To our knowledge, this study is first to demonstrate that CTL responses to endogenous TAAs presented by HLA class I molecules are significantly reduced to undetectable levels solely by the absence of tapasin.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21]24 A former study has demonstrated that restoring tapasin gene expression in a mouse tumor model using viral vector transduction improved survival of model mice bearing lung carcinoma. 28 In this study, we generated human lung and colon cancer variants that express TAAs, survivin, or cep55, genetically lacking tapasin protein expression. To our knowledge, this study is first to demonstrate that CTL responses to endogenous TAAs presented by HLA class I molecules are significantly reduced to undetectable levels solely by the absence of tapasin.…”
Section: Discussionmentioning
confidence: 99%
“…A defect in either component dramatically abrogates peptide loading of MHC-I, resulting in the destabilization of MHC-I complexes and, consequently, low surface MHC-I expression (30,31). TAP1 and TAP2 expression have been associated with the ability of DCs as well as macrophages to cross-present exogenous Ags (32,33). Furthermore, transduction of DCs to express elevated levels of TAP augments their ability to process Ag and results in increased display of viral peptides on surface MHC-I and a greater induction of virus-specific CD8 T cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, defects in the expression and function of antigen-processing machinery (APM) genes may remarkably impair the processing of tumor-associated antigens (TAAs) and the presentation of TAA-derived peptides to CD8 + T cells, thereby providing malignant cells with an immune escape mechanism (6,7). On the basis of this information, we hope to develop a treatment strategy for OSCC that would prevent the escape of tumor cells from immunosurveillance and improve the efficacy of T-cell-based immunotherapy by restoring the normal expression of APM genes (8). Among the components of APM, transporters associated with antigen processing-1 (TAP-1) and the chaperon tapasin play important roles.…”
Section: Introductionmentioning
confidence: 99%